HETEROGENEOUS CONTACT LAYERS FOR INCREASED DYNAMIC RESISTANCE OF THE RAILWAY CROSSING - Schmidová, Eva; Culek, Bohumil; M R, Sunilkumar (Univerzita Pardubice. Dopravní fakulta Jana Pernera, 2019)
Presented work is dealing with the high loaded part of railway svitches or croosings, the prospective ways to increase the operational resistance are discussed. Typical degradation processes of currently widely applied austenitic cast steel are demonstrated by performed failure analyses. The strengthening effect based on the local heterogeneous layer in rail-wheel contact is introduced.
Heterogenní kontaktní vrstvy pro zvýšení dynamické odolnosti železničních křižení
Keywords: railway crossings; železniční křížení; rolling-contact fatigue; gradient steels; wear resistance; kontakní únava; gradientní oceli; odolnost proti opotřebení